The Effect of Capital Expenditure, Sales Growth, And Leverage on Cash Holdings - Halim, Kusuma Indawati; Novianty, Novianty (Jurnal Ilmiah Akuntansi & Bisnis, 2023)
The maintenance of cash holdings is an essential element in ensuring the financial stability of a company. The utilisation of cash holdings might be advantageous for companies seeking to capitalise on investment prospects or finance their expansion strategies. The maintenance of a robust cash holdings enables organisations to promptly capitalise on favourable investment prospects that may emerge within the market. The purpose of this study is to examine the effect of capital expenditure, sales growth, and leverage on cash holdings. The research population is non-cyclical sector companies, totalling 61 companies in Indonesia Stock Exchange (IDX). Data testing was carried out based on secondary data collected, namely the annual reports of each company between 2017 and 2021. The technique used is quantitative by measuring research variables indicators and testing them with statistical analysis. This research utilized a sample of 61 companies that were selected by the purposive sampling method. Multiple regression was used to analyze the data. The findings of this research show that capital expenditure has a negative effect on cash holdings, the sales growth rate has a positive effect on the cash holdings of the company, and leverage has no effect on cash holdings. The findings of this study will provide valuable insights for policy-makers and stakeholders in making informed strategic business decisions regarding cash holdings.